2006
DOI: 10.1186/bf03353382
|View full text |Cite
|
Sign up to set email alerts
|

The 2004 Indian tsunami in Thailand: Surveyed runup heights and tide gauge records

Abstract: Tsunami accompanied with the Sumatra earthquake of 26 December 2004 affected many countries around the Indian Ocean. Thailand located approximately 500 km east of its source, was also severely suffered from the tsunami. From 24 February through 4 March 2005, we surveyed the damaged areas in Thailand from south of Phuket Island up to the border of Myanmar including four islands. The whole coastal area facing the Andaman Sea could be covered. We measured 37 points in total, the tsunami heights are less than 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 1 publication
4
87
0
1
Order By: Relevance
“…Preliminary results of paleotsunami study in Thailand are reported by Fujino et al (2008; and Jankaew et al (2008). The 2004 tsunami height at several locations along Thailand Andaman coast was surveyed by Tsuji et al (2006). Following the 2004 Sumatra-Andaman tsunami there were a few publications detailing paleotsunami study in this area, including Fujino et al, (2009);Jankaew et al, (2008); Monecke et al (2008); Rajendran et al, (2006).…”
Section: Background Research In Paleotsunami Studymentioning
confidence: 99%
“…Preliminary results of paleotsunami study in Thailand are reported by Fujino et al (2008; and Jankaew et al (2008). The 2004 tsunami height at several locations along Thailand Andaman coast was surveyed by Tsuji et al (2006). Following the 2004 Sumatra-Andaman tsunami there were a few publications detailing paleotsunami study in this area, including Fujino et al, (2009);Jankaew et al, (2008); Monecke et al (2008); Rajendran et al, (2006).…”
Section: Background Research In Paleotsunami Studymentioning
confidence: 99%
“…The M w =9.3 Sumatra-Andaman earthquake in December, 2004 ruptured over 1000 km (Krüger and Ohrnberger 2005) and induced a catastrophic ocean-wide tsunami. Run-up heights reached more than 30 m in Aceh, Indonesia (Borrero et al 2006) and nearly 20 m in Thailand (Tsuji et al 2006). Off Java and the Lesser Sunda Islands, devastating tsunamis were induced by the M w =8.3 Sumba earthquake of 1977, the eastern Java earthquake (M w =7.8) of 1994 and the M w =7.7 Pangandaran earthquake in 2006 (ITDB catalogue 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements from tide gauge stations on the coast of Thailand were not used because of inadequate resolution (Fine et al 2005); it is difficult to accurately determine times from these low-speed analog paper records (Rabinovich and Thomson 2007), as the times recorded on some of the sheets are imprecise (Tsuji et al 2006). Deviations between the calculated and observed travel times proved to be satisfactorily small formost of the targets, including those in the open sea and in coastal areas (Table 3).…”
Section: Syntax Accuracy and Dimensional Consistency-mentioning
confidence: 99%